Amino acid residue Y196E substitution and C-terminal peptide synergistically alleviate the toxicity of Clostridium perfringens epsilon toxin. (15th June 2015) - Yao, Wenwu; Kang, Lin; Gao, Shan; Zhuang, Xiangjin; Zhang, Tao; Yang, Hao; Ji, Bin; Xin, Wenwen; Wang, Jinglin
Abstract: Epsilon toxin (ETX) is produced by Clostridium perfringens type B and D strains, and is the causative agent of a lethal enterotoxemia in livestock animals and possibly in humans. However, many details of ETX structure and activity are not known. Therefore, it is important to clarify the relationship between ETX structure and activity. To explore the effect and mechanism of ETX amino acid residue Y196E substitution and C-terminal peptide on toxicity, four recombinant proteins, rETX (without 13 N-terminal peptides and 23 C-terminal peptides), rETX-C (rETX with 23 C-terminal peptides), rETX Y196E (rETX with an amino acid residue substitution at Y196) and rETX Y196E -C (rETX-C with a Y196E mutation), were constructed in this study. Both the amino acid residue Y196E substitution and the C-terminal peptide reduce ETX toxicity to a similar extent, and the two factors synergistically alleviate ETX toxicity. In addition, we demonstrated that the C-terminal peptides and Y196E amino acid mutation reduce the toxin toxicity in two different pathways: the C-terminal peptides inhibit the binding activity of toxins to target cells, and the Y196E amino acid mutation slightly inhibits the pore-forming or heptamer-forming process. Interaction between the two factors was not observed in pore-forming or binding assays but toxicity assays, which demonstrated that the relationship between domains of the toxin is more complicated than previously appreciated. However, the exact mechanism of synergistic action is not yet clarified. Graphical abstract: Highlights: The C-terminal peptide inhibits the binding activity of toxins to target cells. The Y196E mutation inhibits the pore-forming or heptamer-forming process. The C-terminal peptide and Y196E mutation synergistically alleviate ETX toxicity. The rETX Y196E -C protein was a potential candidate vaccine against enterotoxemia.